Glutathione peroxidase-1 regulates adhesion and metastasis of triple-negative breast cancer cells via FAK signaling - Lee, Eunkyung (Redox Biol, 2019)
Triple-negative breast cancer (TNBC) cells, which do not express genes for estrogen receptor (ER), progesterone receptor (PR), and Her2/neu, develop highly aggressive and metastatic tumors resistant to chemo- and hormonal therapies. We found that expression of glutathione peroxidase-1 (Gpx1) is silenced in the non-TNBC cells but significantly maintained in the TNBC cell lines. Such Gpx1 expression plays a vital role in the metastasis of TNBC cells by regulating cell adhesion. Transcriptomic and signaling pathway analyses demonstrate that depletion of Gpx1 essentially impairs cell adhesion/spreading by down-regulating FAK/c-Src activation. Mechanistically, Gpx1 interacts with FAK kinase and prevents the kinase inactivation by H(2)O(2), not lipid hydroperoxide. As a result, depletion of Gpx1 suppresses lung metastasis of TNBC cells in vivo. Overall, our study identifies that Gpx1 is a redox safeguard of FAK kinase and its inhibition may provide an effective way to control the metastasis of deadly malignant TNBC.